Estimation of Natural Circulation Laminar Flow Rate on FASSIP .test loop 04 Based on slope variations Loop 90 o, 75 o, 60 o, 45 o, 30 o - Yuliaji, Dwi; Oktaviandi, Ryan; Waluyo, Roy; Shaari, Norazean Binti; Deendalianto, Deendalianto; Juarsa, Mulya; Raharjo, Esa Putra Ariesta; Cahyati, Nurul (Eximia, 2022)
FASSIP-04 Test Loop is a facility for the investigation of natural circulation flow. Natural circulation flow occurs by different density of fluid with difference temperatures from heat source and heat sink. It is important to investigate capability of heat transfer natural circulation flow with effect variation inclination and variation saturated temperature. Preliminary of flowrate aimed to calculate flow in the FASSIP-04 test loop before the experimental study. Temperature variation of preliminary use saturated water temperature in the heating tank is 50oC, 60oC, 70oC, 80oC, and 90oC also the temperature in cooling tank maintains 10oC every variation experiment. Variation inclination of experiment facility in 45o, 65o, 70o, and 90o. The results of the calculation flowrate shown value is influenced by the difference in temperature in the heater area and cooler area, for the smallest flow rate value is found in the variation of rectangular loop slope of 30o with temperature in the heater area 50o C = 0.22 m / s. while the largest flow rate value is found in the variation of rectangular loop slope 90o with temperature in the heater area 90oC = 0.22 m/s and the maximum Reynolds number in temperature variations 90oC with slope 90o.